Wybrane metody statystyczne w profilowaniu segmentów rynkowych - Jefmański, Bartłomiej (Selected statistical methods in market segments profiling, 2006)
The segmentation procedure does not finish when we have specified the market segments. To satisfy efficiently the needs of the clients defined by the specific segments, we need to discover the factors that diversify clients. Recognising the profile of a given segment allows us to concentrate accurate marketing activities on it. Therefore, defining the profiles of the segments is an important stage of the segmenting procedure. The aim of this study is to use certain statistic methods to create the profiles of the segments. An empirical example will also show methods of interpretation of the obtained results and their usefulness in creating the profiles of the segments. It will also allow comparing the results obtained by using the methods presented in the study.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Taksonomia (13); 2006; nr 1126, s. 397-405